Pengaruh Kesadaran Wajib Pajak, Akses Pajak, Fasilitas Dan Kualitas Pelayanan Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor: Indonesia - Citra Larasati Rochma; Sjarief Hidajat (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2023)
The purpose of this study is to ascertain whether the compliance of motor vehicle tax payers is affected by taxpayer awareness, tax access, facilities, and service quality. The research used in this study is quantitative. Primary data were gathered for this study by the distribution of questionnaires in survey procedures. Incidental sampling is the sampling strategy applied. 100 motor vehicle taxpayers registered at the West Surabaya Samsat Office made up the study's sample. The WarpPLS 7.0 SEM Partial Least Square (PLS) Software was employed for the data analysis process in this investigation. The findings of this study demonstrated that tax access and changeable taxpayer awareness had a substantial impact on motor vehicle tax compliance. Service Quality and tax facilities and has no discernible impact on motor vehicle taxpayer compliance.